Pembinaan Budi Pekerti Siswa melalui Latihan Memanah di Sekolah Menengah Kejuruan Negeri 1 Cikarang Barat - Chevine F Wigatris; Tajudin Nur; Yayat Herdiana (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
This study aims to determine the teacher's efforts in fostering noble character in students at the State Vocational High School 1 Cikarang Barat. How the character and character of students in learning is one of the goals of successful student education. The type of research used is qualitative, with the research subjects being students of the State Vocational High School 1 Cikarang Barat. Data collection techniques in this study were observation, interviews and documentation. Data analysis uses data collection, data reduction, data presentation and drawing conclusions. The results of this study can show that archery activities are able to have a good impact on fostering student character and have an impact on student learning focus optimally. The values ​​identified from this activity are religious values, self-confidence, responsibility, respect for results, discipline and focus. Efforts in character building carried out by the school through archery training are able to have a good impact on students' character